Assessment of Anti–HIV-1 Antibodies in Oral and Nasal Compartments of Volunteers From 3 Different Populations. (1st October 2016) - Bergin, Philip J.; Langat, Robert; Omosa-Manyonyi, Gloria; Farah, Bashir; Ouattara, Gina; Park, Harriet; Coutinho, Helen; Laufer, Dagna; Fast, Pat; Verlinde, Carl; Bizimana, Jean; Umviligihozo, Gisele; et al.
Abstract : Abstract: In this study, we assessed the feasibility of collecting standardized nasal and salivary samples at centers in Nairobi (Kenya), Kigali (Rwanda), and London (United Kingdom) using different collection devices and media (synthetic absorptive matrices versus flocked swabs, and Salimetrics oral swabs versus whole oral fluid collection). We detected anti-Gag (p24) and envelope (gp140) antibodies in both nasal fluid and salivary collections from all HIV-infected individuals, and cross-reactive anti-p24 antibodies were detected in 10% of HIV-uninfected individuals enrolled at one site. Collections from the nasal turbinates were comparable with samples collected deeper in the nasopharyngeal tract, and the yield of anti-p24 IgA in the whole oral fluid samples was higher than in samples collected from the parotid gland. We noted a trend toward reduced levels of anti-HIV antibody in the volunteers receiving anti-retroviral therapy. Levels of antibodies were stable over multiple collection visits. Overall, this study shows that nasal and salivary samples can be collected in a standardized manner over repeated visits in both low- and high-resource settings. These methods may be used in support for future HIV vaccine clinical trials. Abstract : Supplemental Digital Content is Available in the Text.